The tradition of pig hunting in the Minangkabau community - Muhammad Kristiawan, Zainuddin Zainuddin, Zulkifli, (Opción, 2019)
This study investigated the tradition of hunting pigs in Minangkabau, Indonesia. The data were collected through interviews with pig hunting participants and through observation at several hunting locations. It was found that the Minangkabau community, especially pig hunters, did not feel the tradition of hunting pigs was in conflict with the religious Shari’a that they believed. In conclusion, in today’s world, interpretations of religions are no longer isolated, local, and more or less single; rather, many angles of interpretation exist side by side and are accessible to all.